Reduction of aflatoxin level in aflatoxin-induced rats by the activity of probiotic Lactobacillus casei strain Shirota. - Nikbakht Nasrabadi, Elham; Jamaluddin, Rosita; Abd Mutalib, Mohd Sokhini; Khaza'ai, Huzwah; Khalesi, Saman; Mohd Redzwan, Sabran (Wiley, 2013)
Aims: Aflatoxin B1 (AFB1) is considered as the most toxic food contaminant, and microorganisms, especially bacteria, have been studied for their potential to reduce the bioavailability of mycotoxins including aflatoxins. Therefore, this research investigated the efficacy of oral administration of Lactobacillus casei Shirota (LcS) in aflatoxin-induced rats.